IL-10 expression by CT26 colon carcinoma cells inhibits their malignant phenotype and induces a T cell-mediated tumor rejection in the context of a systemic Th2 response - Adris, Soraya (1999)
In spite of the evidence that IL-10 has Th1-immunosuppressive and anti-inflammatory effects, it has been shown that IL-10 may reduce the tumorigenic capacity of certain tumor cell types. In order to characterize the responses elicited by IL-10, we explored the effect of transducing murine CT26 colon carcinoma cells with a recombinant retrovirus expressing mIL-10. IL-10 gene transfer of CT26 cells had no effect on tumor cell growth on plastic surface but inhibited the anchorage-independent growth capacity of tumor cells and their metastatic potential as assessed by their invasive and migration ability. Expression of IL-10 also elicited an antitumor immune response involving both CD4+ and CD8+ T cells. Assessment of the immune status of the animals demonstrated that mice injected with CT26-IL10 cells showed prevalence of a systemic and tumor-specific Th2 response. Spleen cells obtained from these mice showed an increased production of IL-4 and no changes in IFNgamma levels, characteristic of a Th2 response. These results demonstrate that IL-10 affects CT26 tumor cell growth by both inhibiting the malignant phenotype and by recruiting and activating a T cell-mediated antitumor response. This T cell response occurs in the context of a shift towards a Th2 response.